COVID-19 in Kidney Transplant Recipients Vaccinated With Oxford–AstraZeneca COVID-19 Vaccine (Covishield): A Single-center Experience From India. Issue 9 (26th May 2021) - Meshram, Hari Shankar; Kute, Vivek B.; Shah, Nauka; Chauhan, Sanshriti; Navadiya, Vijay V.; Patel, Ansy H.; Patel, Himanshu V.; Engineer, Divyesh; Banerjee, Subho; Rizvi, Jamal; Mishra, Vineet V.
Abstract : : Abstract :